Kristeva’s Impact on Translation and the Interplay of Intertextuality, Transposition and Intersemiosis - Kourdis, Evangelos (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2024)
This essay attempts to present the impact of Kristeva's concepts of intertextuality and transposition on translation studies. The concept of intertextuality contributed significantly to the study of the concept of intersemiosis, although quite often it is difficult to distinguish the two in translation studies. Interestingly, even though intersemiosis or intersemiotic translation is the object of study in translation studies, the translation of intertextuality is a much more prominent focus for translation scholars. At the same time, intersemiosis is considered the most important subject for translation scholars and translation semioticians, who should have the first say. To sum up, Kristeva's important contribution lies in the fact that two important terms, "intertextuality" and "transposition," important terms for the study of literature, have also become objects of study in theoretical and applied translation studies.